2016
DOI: 10.1152/ajpgi.00335.2015
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis alteration within small intestinal mucosa after acute enteral refeeding in total parenteral nutrition mouse model

Abstract: Feeding strategies to care for patients who transition from enteral nutrient deprivation while on total parenteral nutrition (TPN) to enteral feedings generally proceed to full enteral nutrition once the gastrointestinal tract recovers; however, an increasing body of literature suggests that a subgroup of patients may actually develop an increased incidence of adverse events, including death. To examine this further, we studied the effects of acute refeeding in a mouse model of TPN. Interestingly, refeeding le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…As in this zebrafish model, tgfβ has been noted to rise with refeeding in the mouse model noted above [34]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in this zebrafish model, tgfβ has been noted to rise with refeeding in the mouse model noted above [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, dkk3 (2.3 log 2 FC), a secreted Wnt antagonist, was also increased. In a study of enteral atrophy followed by refeeding and therefore epithelial expansion in the mouse, wnt5A , cyclin D1 and c-Myc all decline without enteral nutrition and then are restored with the reintroduction of enteral nutrition and the subsequent adaptive response [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Loss of enteral nutrition through long-term caloric depletion, fasting, or parenteral nutrition can alter the function of ISC/progenitor populations as well as that of other accessory cells in the intestinal stem cell niche such as Paneth cells 66, 67, 68. Previous studies have shown that phosphatase and tensin homolog, a negative regulator of the PI3K/AKT/mammalian target of rapamycin complex 1 (mTORC1)-signaling pathway, is an important regulator of reserve facultative ISCs 67 .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite its advantages, evidence is accumulating that TPN, especially long‐term TPN, may lead to increasing associated complications like gut‐derived infections due in part to disruption of intestinal barrier function. To date, although the underlying mechanisms of intestinal barrier dysfunction have not been fully elucidated, a number of possible contributing factors have been reported in a rodent model of TPN, including aberrant signaling pathways in enterocyte proliferation/apoptosis, decline in mucosal immunity, dysbiosis, and cascade of inflammatory cytokines leading to disassembly of tight junctions . However, the question is, in addition to all those contributing factors that appear with the development of intestinal barrier dysfunction, whether there exists something else that occurs much earlier and triggers the disruption of barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…To date, although the underlying mechanisms of intestinal barrier dysfunction have not been fully elucidated, a number of possible contributing factors have been reported in a rodent model of TPN, including aberrant signaling pathways in enterocyte proliferation/ apoptosis, [25][26][27] decline in mucosal immunity, 28,29 dysbiosis, and cascade of inflammatory cytokines leading to disassembly of tight junctions. 30,31 However, the question is, in addition to all those contributing factors that appear with the development of intestinal barrier dysfunction, whether there exists something else that occurs much earlier and triggers the disruption of barrier function. Recently, intestinal P-gp has been considered as a natural defense mechanism that antagonizes the translocation of harmful substances from the gut to circulation via transcellular route.…”
Section: Discussionmentioning
confidence: 99%